Engagement in Youth Athletes as a Positive Experience in Sport: Implications of Gender, Age, and Competitive Level - María Julia Raimundi; Ignacio Celsi; Mauro Pérez-Gaido; Vanina Schmidt; Isabel Castillo; Octavio Alvarez (MDPI AG, 2024)
The aim of this study was to examine athlete engagement and its relationships with indicators of the quality of the athlete's sport experience, exploring potential differences according to gender, age, and competitive level. Furthermore, this study validated the Athlete Engagement Questionnaire (AEQ) in young athletes and confirmed its factor structure. A total of 1188 athletes (43.90% girls) from Argentina participated in the study, with a mean age of 15.92 (SD = 2.50). The participants completed the AEQ along with other measures of athletes' quality of experience, such as motivation, enjoyment, and burnout. This study confirmed the multidimensional nature of engagement, showing positive associations with high-quality athlete experiences and revalidating the inverse relationship with burnout. Moreover, the study found differences in engagement dimensions (i.e., confidence, vigor, dedication, and enthusiasm) based on the interplay of gender, age, and competitive level. In general, male athletes, younger athletes, and those with a higher competitive level showed more engagement and interactions between these sociodemographic variables. The Argentinian version of AEQ exhibited optimal fit and reliability and good indexes of measurement invariance across gender, age, and competitive level. These findings validate the AEQ as a reliable tool for evaluating sport engagement among adolescents in Argentina. Engagement constitutes an indicator of an optimal experience linked to positive youth development through sports participation.